Increasing Service Utilization of An Outpatient Breastfeeding Clinic - Szeles, Heather (My University, 2023)
Breastfeeding is highly recommended by the World Health Organization, Centers for Disease Control, and the American Association of Pediatrics (CDC, 2020; WHO, 2014; Meek & Noble, 2022). One goal of Healthy People 2030 is to increase breastfeeding rates (Office of Disease Prevention and Health Promotion [ODPHP], 2020). An outpatient breastfeeding clinic was established as a patient resource in this medium-sized community hospital. The purpose of this facilities clinic was to provide a resource to the community to support new parents and their breastfeeding goals. The organization determined that there needed to be more knowledge among staff nurses regarding the existence and role of this clinic. This quality improvement project was developed to educate staff nurses working in inpatient obstetrics and postpartum on the availability and benefits of the outpatient breastfeeding clinic to prepare them to educate their patients better. Implementing this quality improvement in nursing education led to a substantial increase in patient utilization of this clinic from the previous year. From January through April 2022, the utilization rate of this clinic was 8%, whereas, during implementation in January through April 2023, the utilization rate was 37%. Educating nurses on the benefits of the outpatient breastfeeding clinic can help facilitate better outcomes for patients who desire to breastfeed for the first year of their child’s life. Access to and knowledge of outpatient resources can improve overall breastfeeding practices in the local community.
Keywords: breastfeeding, outpatient, education, nurses, quality improvement, community hospital, labor and delivery, postpartum